Adult Education Adrift in a Net: Making Waves or Clutching a Lifering? - Roger Boshier [Convenor]; Mary Wilson; Byron Burnham; Patricia Reeves (Adult Education Research Conference, 1999)
The Internet and World Wide Web exemplify values advanced by heroic adult education theorists such as Ivan Illich. They have also triggered a deluge of hyperbole and surfeit of false dichotomies (e.g. online versus face-to-face education). But, in the chorus of critics and advocates, adult educators have been noticeably silent. This symposium is designed to rectify this situation by interrogating Internet and Web learning and education from an "adult education" perspective.